Khilafiyah dan Perbandingan Mazhab - Anhar .; Irnawati Muhajir; Sri Wahyuni; Abbas Baco Miro; Ahmad Nashir (CV. ITTC INDONESIA, 2026)
Khilafiyah is a phenomenon inseparable from the dynamics of legal and theological thought in Islam. Differences of opinion among scholars arise as a consequence of various methods of interpreting the Qur'an and Hadith, and are influenced by historical, social, and cultural factors. This study aims to analyze the concept of khilafiyah and the comparison of schools of thought in Islam, identify the factors causing the emergence of differences of opinion, and examine their impact on religious practices and the social life of Muslim communities. This study uses a qualitative approach using literature studies, interviews with scholars and community leaders, and observations of religious practices within Muslim communities. Data are analyzed descriptively and analytically to gain a comprehensive understanding of khilafiyah and the dynamics between schools of thought. The results show that khilafiyah reflects not only differences in fiqh but also in theology, ethics, and worship practices. While potentially causing conflict, khilafiyah also has a positive role in enriching the intellectual treasury of Islam and fostering tolerance when addressed wisely. Therefore, an inclusive and dialogical understanding of khilafiyah and comparison of schools of thought is an important key in maintaining harmony and unity of Muslims in a pluralistic society.